ChargeSwitchTM-coated 96-well plates: Genomic DNA purification, amplification and detection in a single well. Crow M., Leadsham J., Cheshire Z., Harper G., Olivares E., Oak S., Lee B., Baker M., Peterson T., Invitrogen, Carlsbad, CA, USA. - Garry Harper (American Association of Clinical Chemistry., 2006)
2006 Annual Conference OakRidge Abstract 29.